Analysis Of Yttrium Iron Garnet (Yig) Resonator With Excess Fe2o3 For Wideband Antenna Applications - Othman, Mohamadariff (2015)
Satellite communications play an important role in telecommunications. Realizing this fact, broadband antennas are part of the solution to establish a concept of wide frequency usage in satellite technology. Wideband dielectric resonator antenna (DRA) provides better efficiency and miniaturization as compared to the metallic antenna. However, having dielectric resonator (DR) with different permittivity (εr) and size contributes to the increase in the complexity of DRA design and fabrication. Besides, every time to use new dielectric material, it must be fully characterized. This is considered redundant prior to the DRA analysis. Therefore, the intent of this work is to realize efficient wideband antenna and rapid antenna analysis. Improvement to the wideband DRA is done using unbiased low permittivity yttrium iron garnet (YIG) with excess Fe2O3 to produce cylindrical resonator with the same dimension but different εr. YIG resonator was developed by using solid state reaction method and characterized by x-ray diffraction (XRD), field emission scanning electron microscopy (FESEM) and high performance probe (Agilent 85070E) dielectric probe kit. Based on the characterization result, curve fitting model (CFM) was modified using Minitab software which applies least square method of correlation and regression analysis. Simulations of the YRA structures were carried out using Computer Simulation Technology (CST) Microwave Studio software while measurement of the S-parameters as well as gain were analyzed using the PNA-X xxiii Network Analyzer (8720D, 10MHz-50GHz). The radiation pattern of the YRA was tested by using 10 meter anechoic chamber. XRD and FESEM analysis give indication on fully reacted, dense and solid cylindrical YIG using solid state method. Using different amount of excess Fe2O3 create low εr YIG within the range of 10.04 to 17.36 with low tan δ value. Correlation between εr and excess Fe2O3 is used to modify the curve fitting equations. The modified equation provides rapid analysis on YIG antenna by including the presence of excess Fe2O3 instead of εr value. Correlation coefficient of -0.862 indicates the strong correlation between εr and excess Fe2O3. Determination coefficient, R2 of 99.6% indicates that the curve of the generated equation is fit with εr data. Hypothesis testing with high p-value over 99% verifies that modified equation is well match with the original equations. The fabricated YIG resonators and modified equations are used together to produce wideband stacked YIG resonator antenna (YRA). Three stacked YIG with different combination of excess Fe2O3 provide the proposed wideband YRA. YIG resonators with excess Fe2O3 of 8% (YR8), 14% (YR14) and 17% (YR17) present the best YR combinations with frequencies of 17.25 GHz, 19.18 GHz and 20.81 GHz, respectively. The combinational effect of three YIG resonators produces bandwidth of 24.22% measured at -10 dB impedance bandwidth centered at 19.25 GHz. Load impedance of YRA is well-match with input impedance of 50 Ω. Findings also indicate identical radiation pattern of HE11 mode throughout the desired frequency range. The stacked wideband YRA has average gain of 7.49 dB over the frequency range. In conclusion this work offers an improved, efficient and relatively simple YRA using YIG resonator with excess Fe2O3 and modified curve fitting equation.